2020
DOI: 10.1021/acs.est.9b07018
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for the Quantification of Different Inorganic and Organic Phosphorus Compounds in Environmental Samples by P L2,3-Edge X-ray Absorption Near-Edge Structure (XANES) Spectroscopy

Abstract: Phosphorus (P) is an essential element for life on Earth, with an important and oftentimes unaccounted organic biogeochemical component. Current methods for the quantification of different organic P compounds in environmental samples (e.g., soils, sediments) are based on extraction techniques and often associated with incomplete P recovery or sample changes. In this study, we present a protocol for the quantification of different organic and inorganic P species in soils using synchrotron-based X-ray absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This analytical method allows for characterisation of the speciation (coordination and redox state) of the main elements of mineralised hard tissues (here, Ca and P in calcium phosphates) as well as associated carbonate ions and organic molecules. The combination of XANES and synchrotron radiation, a source of high-intensity polarised X-rays in a given energy range, facilitates studies at the angstrom level, which opens up new horizons for understanding biomineralisation processes [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This analytical method allows for characterisation of the speciation (coordination and redox state) of the main elements of mineralised hard tissues (here, Ca and P in calcium phosphates) as well as associated carbonate ions and organic molecules. The combination of XANES and synchrotron radiation, a source of high-intensity polarised X-rays in a given energy range, facilitates studies at the angstrom level, which opens up new horizons for understanding biomineralisation processes [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…And the P atoms in AuCs/BP‐NG and AuNPs/BP‐NG all got electrons along with the peaks moving to lower energies. [ 27 ] It could be deduced that Au nanoclusters had strong chemical interaction with N and P atoms. The comparison of high‐resolution XPS results of N 1s (Figure 2d) among APTMS/BP‐NG, AuCs/BP‐NG, and AuNPs/BP‐NG showed that the peaks of AuCs/BP‐NG shifted to lower energy with obtaining electrons, with the noticeable shape change, but that peaks in AuNPs/BP‐NG had no obvious change.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge this is the first STXM study performed using X-ray absorption spectroscopy at the P K-edge. For chemical specificity the P L 2,3 -edge is more sensitive, 16 but its low energy (133 eV) would require thin (100 nm) samples, with a risk of losing unbound P in the algae during sample preparation. Here, in contrast, complete algae could be measured, without any further preparation.…”
Section: ■ Introductionmentioning
confidence: 99%